2018
DOI: 10.18551/rjoas.2018-08.54
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Climate Change Impact of Soil Moisture Availability in the Dry Land Corn Fields of Sumbawa Regency, Nusa Tenggara Barat Province

Abstract: Climate change has great impact on the availability of soil moisture for the production of food crops in the drylands. Objective of the research was to study climate change simulations on the availability of soil moisture in dry land in Unter Iwes District, Sumbawa Regency, West Nusa Tenggara Province.The method used for water balance calculations was Thornthwaite-Mather. Evapotranspiration calculations use the Penman Monteith model on the CROPWAT 8.0 model. The level of groundwater availability was obtained b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
1
0
2
Order By: Relevance
“…Peningkatan produksi bawang merah Kabupaten Sumbawa didukung oleh luas tanam yang terus meningkat, terutama dengan pemanfaatan lahan kering dataran tinggi. Lahan kering merupakan salah satu sumberdaya lahan sub optimal yang dapat dimanfaatkan untuk pengembangan pertanian (Ayu et al, 2013). Namun, pengembangan usahatani bawang merah dataran tinggi menghadapi permasalahan dalam peningkatan produksi, meliputi kemampuan teknologi budidaya yang masih konvensional, harga yang fluktuatif (Iriani, 2013), dan peningkatan biaya produksi (Yulyatin et al, 2019).…”
Section: Pendahuluan *unclassified
“…Peningkatan produksi bawang merah Kabupaten Sumbawa didukung oleh luas tanam yang terus meningkat, terutama dengan pemanfaatan lahan kering dataran tinggi. Lahan kering merupakan salah satu sumberdaya lahan sub optimal yang dapat dimanfaatkan untuk pengembangan pertanian (Ayu et al, 2013). Namun, pengembangan usahatani bawang merah dataran tinggi menghadapi permasalahan dalam peningkatan produksi, meliputi kemampuan teknologi budidaya yang masih konvensional, harga yang fluktuatif (Iriani, 2013), dan peningkatan biaya produksi (Yulyatin et al, 2019).…”
Section: Pendahuluan *unclassified
“…Edukasi penanganan pasca panen sangat penting diberikan kepada petani pemula yang mengusahakan budidaya bawang merah utamanya di lahan kering dataran tinggi. Ayu et al (2019) menjelaskan bahwa usahatani lahan kering memiliki banyak kendala, sehingga peningkatan kapasitas petani adalah faktor penting pendukung keberhasilan peningkatan produksi lahan kering. Petani muda harus memiliki kemampuan untuk, memahami pertanian sebagai bisnis dan menjadi seorang pembelajar telah menjadi keharusan bagi petani muda agar dapat bertahan dan berkembang dalam bisnis pertanian (Lans et al, 2017).…”
Section: Pendahuluanunclassified
“…Research results from Indonesia's territory showed that Philip's infiltration model worked well upstream of the Progo watershed, Indonesia [5]. The Horton infiltration model performed well at 18 observation points of infiltration rates on dry and rainfed land [6]. Furthermore, the Horton infiltration model proved to be better than Philip's and Kostiakov's models in predicting infiltration rates from 12 observation points on agricultural land in the Merawu Watershed, Banjarnegara [7].…”
Section: Introductionmentioning
confidence: 99%